Study on a near-zero emission SOFC-based multi-generation system combined with organic Rankine cycle and transcritical CO2 cycle for LNG cold energy recovery. (1st February 2022) - Liang, Wenxing; Yu, Zeting; Bai, Shuzhan; Li, Guoxiang; Wang, Daohan
Highlights: A novel SOFC-based multi-generation system is proposed. The system can realize CO2 capture with low energy consumption. LNG cold energy is recovered in a cascade way. The unreacted anode gas of SOFC is burned with O2 instead of cathode gas. Abstract: This study proposes a near-zero emission SOFC based multi-generation system integrated with organic Rankine cycle and transcritical carbon dioxide cycle, and a LNG cold energy utilization system is also introduced in order to realize CO2 condensation and cryogenic capture. In the proposed system, the unreacted anode gas of SOFC is burned with pure oxygen instead of cathode gas by which it can provide the possibility for the follow-up CO2 capture at low energy consumption assisted by LNG cold energy utilization. The novel poly-generation system can realize the cooperative production of the energy (cooling, heating and power output), and the matter (condensate recovery and captured CO2 ). The energy and exergy analysis are performed to investigate the proposed system performance based on the established steady-state model. The results reveal that, under the design conditions, the thermal efficiency, net electrical efficiency and exergy efficiency of the proposed system achieve 90.99%, 55.01% and 53.07%, respectively. And the amount of CO2 captured, condensate recovery, and natural gas supply reach 5219.21 ton/year, 1324.83 ton/year and 4273.13 ton/year, respectively. Moreover, the exergy analysis shows that the exergy loss proportion of SOFC top cycle accounts for 47.3% of the total losses. Parameters analysis indicate that the electrical efficiency and the exergy efficiency are increased first and then decreased, and achieve the maximums at the SOFC inlet temperature of 554.4℃ and the operating pressure of 650 kPa, respectively. In addition, it is observed that the variation of steam-to-carbon ratio ( STCR ) has little effect on electrical efficiency and exergy efficiency, but has obvious effect on thermal efficiency. It is also found that the cooling, heating and power output are increased, but all the efficiencies are decreased as current density increases.